Algorithmic Amplification, Religious Authority, and Electoral Polarization in Indonesia’s Digital Democratic Public Sphere - Ahmed El-Sayed Hassan (PENA KREATIF PUBLISHER, 2026)
Digital political communication in Indonesia increasingly unfolds through platform infrastructures that rank, recommend, and amplify morally charged content. In this environment, religious authority has become deeply entangled with electoral messaging, partisan identity, and the visibility dynamics of social media platforms. This article examines how algorithmic amplification interacts with religious authority to intensify electoral polarization in Indonesia. The article adopts a qualitative and theory-driven approach grounded in affective polarization studies, digital religion scholarship, and platform governance analysis. It draws on academic literature, policy materials, platform-related discussions, and publicly accessible digital political-religious communication relevant to Indonesian electoral contestation. Analytical attention is directed to algorithmic amplification, religious authority signaling, moral monism, network segregation, and strategic political mobilization. A mechanism-based synthesis is used to clarify how these processes reinforce one another in digitally mediated democratic conflict. Religious authority emerges as a powerful amplifier of partisan distinction when platform systems reward emotionally charged and morally coded political communication. Electoral polarization therefore becomes more intense when algorithmic visibility converts religious claims into recurrent signals of ethical belonging and political exclusion. The article contributes to the field by offering an integrated framework for understanding how digital infrastructures, moral authority, and democratic polarization interact in contemporary Indonesia.